Green Human Resources Management and Employee Engagement in Nepalese Commercial Banks - Kanaujiya, Nabin (Nexus: Journal of Interdisciplinary Engineering, Technology and Management, 2026)
This study examines the impact of Green Human Resource Management practices on employee engagement in Nepalese commercial banks amid increasing global concern for climate change and sustainability. Although banks are not direct polluters, their operations, energy consumption, paper use, e-waste generation, and lending decisions significantly affect environmental sustainability. Following Nepal’s commitment to the Sustainable Development Goals, financial institutions are increasingly expected to adopt environmentally responsible practices. However, limited empirical evidence exists regarding the implementation of GHRM in Nepal’s banking sector. Using a quantitative cross-sectional research design, primary data were collected from 363 employees, including managers, officers, and clerks, from selected commercial banks in Kathmandu district through purposive sampling. Data were analyzed using Structural Equation Modeling with SmartPLS software. Reliability and validity tests confirmed strong measurement consistency, with Cronbach’s alpha values ranging from 0.781 to 0.945. Green training and development and green performance management emerged as the most reliable and influential dimensions affecting employee engagement. The findings support that GHRM practices positively and significantly influence employee engagement in Nepalese commercial banks. The study highlights that integrating environmental concerns into HR policies strengthens workforce commitment and organizational sustainability performance. Practical implications suggest that banks should prioritize green training programs and environmental performance appraisal systems. The research also contributes academically by extending the Ability-Motivation-Opportunity Theory to the banking sector in South Asia. It provides one of the earliest empirical studies on GHRM within Nepalese commercial banking institutions.